2013
DOI: 10.1088/2041-8205/771/2/l19
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Evolution of Star-Forming Galaxies Over the Last 11 Billion Years

Abstract: We calculate the stellar mass-metallicity relation at five epochs ranging to z ∼ 2.3. We quantify evolution in the shape of the mass-metallicity relation as a function of redshift; the mass-metallicity relation flattens at late times. There is an empirical upper limit to the gas-phase oxygen abundance in star-forming galaxies that is independent of redshift. From examination of the mass-metallicity relation and its observed scatter we show that the flattening at late times is a consequence of evolution in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
264
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(297 citation statements)
references
References 49 publications
(71 reference statements)
30
264
2
1
Order By: Relevance
“…These authors reported good agreement between their findings and the evolution of the MZR obtained from the EAGLE high-resolution simulation Recal-L025N0752. Guo et al (2016) also found a good agreement between the M * -O/H| SF,gas relation derived from this simulation and observations by Zahid et al (2013a) at z 1. At 1 z 2, the latter authors obtained a slightly lower level of evolution (by ≈0.2 dex) in simulations with respect to observations 4 (the reader is referred to Guo et al 2016 for a comparison between EAGLE results and predictions from some semi-analytical models).…”
Section: Evolution Of the M * -Z Sfgas Relationsupporting
confidence: 78%
See 1 more Smart Citation
“…These authors reported good agreement between their findings and the evolution of the MZR obtained from the EAGLE high-resolution simulation Recal-L025N0752. Guo et al (2016) also found a good agreement between the M * -O/H| SF,gas relation derived from this simulation and observations by Zahid et al (2013a) at z 1. At 1 z 2, the latter authors obtained a slightly lower level of evolution (by ≈0.2 dex) in simulations with respect to observations 4 (the reader is referred to Guo et al 2016 for a comparison between EAGLE results and predictions from some semi-analytical models).…”
Section: Evolution Of the M * -Z Sfgas Relationsupporting
confidence: 78%
“…EAGLE highresolution simulations have also been found to predict an evolution of the MZR consistent with the observational trend reported by Zahid et al (2013a) (e.g. Guo et al 2016).…”
Section: Introductionsupporting
confidence: 78%
“…The mass-metallicity relation by Tremonti et al (2004) is often used as a benchmark for comparisons with similar relations obtained for low-z and high-z galaxies (e.g. Lee et al 2006;Maiolino et al 2008;Amorín et al 2010;Manucci et al 2010;Maier et al 2014;Steidel et al 2014;Zahid et al 2011Zahid et al , 2012Zahid et al , 2013Zahid et al , 2014a. However, we note that Tremonti et al (2004) selected all star-forming galaxies, including galaxies with low-excitation H ii regions, while only galaxies with high-excitation H ii regions are present in high-z samples.…”
Section: Introductionmentioning
confidence: 74%
“…Ho et al 1993a;Groves et al 2004), and then select the metallicity and ionization parameter values which produce the best correspondence between the theoretical and observed mixing sequence for each galaxy. It is important to note that the metallicity and ionization parameter are degenerate quantities, such that a more enriched, higher ionization model can produce the same line ratios as a more pristine, lower ionization model (Kewley et al 2001(Kewley et al , 2013a. Detailed diagnostics employing a larger range of emission lines are required in order to discriminate between these degenerate scenarios.…”
Section: Constraints On Model Parametersmentioning
confidence: 99%